Mapping Research Trends in Translanguaging in English Language Teaching: A Scopus-Based Bibliometric Analysis - Belly Ubaidila; Rizka Safriyani (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2026)
This study employed bibliometric analysis to present trends in the development of translanguaging research in English Language Teaching (ELT) on the Scopus database from 2014 to 2026. The study aims to systematically map annual scientific production, most productive authors, most productive sources, most relevant affiliations, most cited countries, keyword co-occurrence networks, and thematic maps. A descriptive quantitative method was used, with a final dataset of 437 Scopus-indexed journal articles from 2014 to 2026 (partial records), using the keyword